Design and Development of a Solar and Hand-Cranked Dynamo-Based with Battery Storage for Low Power Device Charging - Subramaniam, Vaishinavi; Md Nor Ramdon Bin Baharom (Progress in Engineering Application and Technology, 2026)
This project addresses the dual challenges of urban sedentary behaviour and the demand for sustainable public energy infrastructure through the design and development of a Hybrid Solar-Kinetic Charging Station at Tanjung Emas Park, Muar. Unlike traditional charging kiosks, this system implements a "Smart Exercise Clause," requiring users to maintain a physical effort of 50 RPM to unlock the 5V USB charging output. The hardware architecture integrates a 10W Solar Photovoltaic panel with a high torque (1.5Nm) NEMA 23 Bipolar Stepper Motor used as a kinetic harvester. A critical technical challenge of converting low-RPM mechanical energy into stable DC power was solved using a Greinacher Voltage Doubler circuit optimized with Schottky diodes. Experimental results demonstrated that the use of Schottky diodes minimized forward voltage loss, achieving a stable output at the target speed, providing sufficient headroom for a 5V regulator The system is governed by an Arduino Nano microcontroller, which utilizes a Hall Effect sensor to monitor rotational speed and calculates real-time calorie expenditure. Data analysis from the prototype confirms that the "Exercise Clause" successfully disrupts sedentary behaviour by gamifying energy production, while the hybrid design ensures power availability in the shaded riverside environment of Tanjung Emas. The findings suggest that this "Play-to-Charge" model provides a viable, off-grid solution for promoting public health and renewable energy awareness within the Malaysian municipal landscape.